On the decay, preservation and restoration of imported Portuguese Christian missionary vocabulary in the Kyushu district of Japan since the 16th century - Ogawa, Shunsuke (Slavia Centralis, 2020)
The aim of this paper is to elucidate the history of the decay, preservation and restoration of imported Portuguese Christian missionary vocabulary in the Kyushu district of Japan since the 16th century. In conclusion, the following can be pointed out: 1) almost all words have generally decayed. 2) parts of the words are used as general nouns with discriminatory meaning. 3) Some people still try to preserve these words against the guidance of Catholic priests. 4) Recently, parts of the words have started to be used as the names of some alcoholic drinks and sweets. Thus, in this district, the number of people who use these words has been increasing again. This is the restoration of imported Portuguese Christian missionary vocabulary.